How Does Economic Policy Uncertainty Affect Performance and Risk?Evidence from the U.S. Banking Industry - Yang, Lan (2019)
Abstract Using the data of U.S. banks from 2007 to 2018, this paper investigates how economic policy uncertainty affects the performance and risk of banks. This study shows that when the uncertainty of economic policy increases, there is a significant negative impact on the bank’s accounting performance and market valuation. Also, this study finds that the bank’s stability has been significantly weakened by the rise of economic policy volatility. It is worth noting that small banks are more vulnerable in the face of uncertainty, because of less information accessibility; and the large banks are ‘too-big-to-fail’, so they are more likely to receive financial rescues than small banks. Further analysis implies that maintaining a high level of capitalization can partially offset adverse impacts, and the drop of market growth begin to become more pronounced after the financial crisis. Therefore, this study suggests that banks should maintain adequate capital to cope with unexpected policy fluctuations, and governments should not ignore the importance of small bank’s stability. Moreover, prudential, transparent, informative, and consistent policies are beneficial to a bank’s profitability and safety. Keywords: Economic policy uncertainty, performance, stability, financial crisis